Staging repair - Danish Sheikh (Law Text Culture, 2021)
This paper articulates “repair work” – drawing from Eve Sedgwick’s concept of reparative reading – as a jurisprudential activity. In the late 90s, Sedgwick urged her scholarly community to invest in reparative readings as a contrast to the prevalent hermeneutics of suspicion. The reparative impulse, she wrote, “is additive and accretive …. it wants to assemble and confer plenitude on an object that will then have resources to offer to an inchoate self”. A commitment to reparative reading entails an openness to surprise, to the rendering of the self as vulnerable, to the potentially traumatic experience of hope. In this paper, I describe how a material and theatrical jurisprudence imbricated within the body might give us the tools to perform repair. I anchor my paper on a descriptive experience of the 2016 Indian performance piece Queen Size. At a time when homosexuality was a criminal offence in the country, this was a show which staged a joyful dissent against the law, centering around the public display and celebration of an act of queer intimacy. I read this performance in conversation with Robert Cover’s celebrated essay “Nomos and Narrative” and a 1934 sodomy trial before the High Court of Sindh. Reassembling these texts, I pay attention to how each of them are staged, along with my own restaging. This form of dramaturgical attention allows me to forage and weave together seemingly disparate objects that vary in time, genre and form. In the process, it allows me to stage a jurisprudence of repair.